(3aJM GdeLjO aj bQGAI YGUe ef WQjb GdbUjO aj GdJLhjOs - (3eMeO Hf MSf Hf eMeO Hf CMeO GdSefhOj, GdefjQ,J (B1199 (3g` s ((3EHQGgje MSf CMeO YeQ s)
(3ChdgG (B:s
(3CeG HYO agPg QSGdI aj QhGjI MaU Yf YGUe ef WQjb YHjO Hf GdUHGM GdJj gj WQjb GdEeGe Hj GdbGSe GdTGWHj s
(3BNQgG (B:s
(3hcGf GdaQGZ ef JYdjbg fgGQ GdLeYI GdeHGQc s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI s
Keywords: (3GdbQGAGJ hGdJLhjOs